A country of vast designs : James K. Polk, the Mexican War, and the conquest of the American continent - Merry, Robert W., 1946- (New York : Simon & Schuster, 2009)
Merry examines how, in a one-term presidency, James K. Polk completed the story of America's Manifest Destiny by expanding its territory across the continent.
Includes bibliographical references (pages 479-550) and index.
Keywords: Polk, James K. -- 1795-1849.; Polk, James K. -- 1795-1849.; Polk, James K. -- 1795-1849.; Polk, James Knox, -- 1795-1849.; Presidents -- United States -- Biography; United States -- Politics and government -- 1845-1849.; United States -- Territorial expansion -- History -- 19th century; Politics and government; Presidents; Territorial expansion; United States; Territoriale conflicten; Expansie (macht); Staatsvorming; Verenigde Staten; Mexico; United States -- Politics and government -- 1845-1849.; United States -- Territorial expansion -- History -- 19th century; 1800 - 1899; Biographies; Biography; History